Penentuan Harga Pokok Produksi Minuman Pada Kedai Kopi Social Samarinda - Paulina, Debby; Salman, Putriana; Julkawait (Indonesian Journal of Applied Accounting and Finance, 2022)
The purpose of this study is to calculate the cost of goods manufactured of beverages at the Kedai Kopi Social Samarinda using the full costing method. The problem in this study is that the cost of goods manufactured calculated by the company is still not correct. The research method used is a qualitative method with data analysis techniques, namely quantitative descriptive and the samples used are 5 best-selling product variants. The results of the study show that the calculation of the cost of goods manufactured using the full costing method has a greater value than the company's calculation, because the company does not calculate production costs in detail, so that the profit earned tends to be greater. The implication of this research is that the company can calculate the cost of goods manufactured correctly, so that it can generate maximum profit.